Significant repetition probability effects in schizophrenia. (30th August 2019) - Kovács, Gyula; Grotheer, Mareike; Münke, Lisa; Kéri, Szabolcs; Nenadić, Igor
Highlights: We found a significant RS in the fusiform and occipital face areas, as well as in the lateral occipital cortex that was similar in both healthy control and schizophrenia patient groups. We observed similar repetition probability effects (larger RS in blocks with high frequency of repetitions than in blocks with low repetition likelihood) in both subject groups as well. Repetition reduces the top-down ε for expected, compared to unexpected stimuli in patients with schizophrenia as well. Abstract: Background: A growing body of evidence suggests that the comparison of expected and incoming sensory stimuli (the prediction-error (ε) processing) is impaired in schizophrenia patients (SZ). For example, in studies of mismatch negativity, an ERP component that signals ε, SZ patients show deficits in the auditory and visual modalities. To test the role of impaired ε processing further in SZ, using neuroimaging methods, we applied a repetition-suppression (RS) paradigm. Methods: Patients diagnosed with SZ ( n = 17) as well as age- and sex- matched healthy control subjects (HC, n = 17) were presented with pairs of faces, which could either repeat or alternate. Additionally, the likelihood of repetition/alternation trials was modulated in individual blocks of fMRI recordings, testing the effects of repetition probability (P(rep)) on RS. Results: We found a significant RS in the fusiform and occipital face areas as well as in the lateral occipital cortex that was similar in healthy controls and SZ patients SZ. More importantly, we observed similar P(rep) effects (larger RS in blocks with high frequency of repetitions than in blocks with low repetition likelihood) in both the control and the patient group. Conclusion: Our findings suggest that repetition_probability modulations affect the neural responses in schizophrenia patients and healthy participants similarly. This suggests that the neural mechanisms determining perceptual inferences based on stimulus probabilities remain unimpaired in schizophrenia.